SYNTHESIS AND LUMINESCENT INVESTIGATION ON THE CALCIUM SILICATE CA3 SI 2 O7 , ACTIVATED WITH EU2+ IONS - S. M. Levshov; I. P. Kovalevskaya; N. P. Efryushina; Z. D. Klimenko; V. P. Dotsenko (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2014)
The thermodynamic analysis of possible chemical processes occurring in the system CaO:SiO2=3:2 was carried out. Optimized conditions for the preparation Ca3(1-х)Eu3xSi2O7 firm solutions have been determined. It was shown that the effective luminescence of Eu2+ions in Ca3Si2O7 with a maximum at 625 nm creates pre-conditions for the use of this material as a phosphor for white light-emitting diodes.